Marketing strategies for the promotion of construction enterprises on the thermometernization market - Maksymov, A.S.; Moholivets, A.A.; Kyrylov , I.V. (Ways to Improve Construction Efficiency, 2024)
The thermal retrofit market opens up significant opportunities for construction enterprises due to the growing emphasis on energy efficiency and sustainability in construction. To capitalize on this opportunity, construction companies must develop marketing strategies that address different aspects of the market and address diverse customer needs. Digital marketing platforms are changing the role of promoting construction enterprises in the thermo-modernization sector. By using websites, social networks and online advertising, companies can effectively showcase their expertise, highlight successful projects and reach a wider audience. Creating engaging and informative content such as blogs, videos and infographics about the benefits of retrofitting can educate potential customers and position your company as a leader in the field. This training approach will help build trust and credibility, making it more likely that clients will demand their services. A personalized and customer-oriented approach is the number to convince successful customers to invest in thermal modernization. Tailoring solutions to meet specific customer needs and highlighting the long-term cost savings and environmental benefits of these upgrades can be a powerful motivator. Social proof in customer lists and case studies are places to build a reputation for reliability and success in the retrofit market. Demonstration of real examples of successful projects, possible and satisfied customers, can convince customers of the effectiveness of the quality of the company and the tangible benefits of its services. Detailed case studies that outline the challenges, solutions and outcomes of past projects can provide a clear picture of what new clients can expect. A comprehensive marketing strategy of the construction enterprise market for thermal modernization should combine digital marketing, strategic services, personalized approaches to customers, an emphasis on sustainability, social sustainability and innovative methods of engagement. By integrating these, companies can provide services, build reputation and attract repeat customers looking for elements of energy-efficient and sustainable building solutions.